Intervensi Keperawatan Non Farmakologis Kompres Hangat Pada Klien Dengan Nyeri Akut Gastritis - Putri Wulandini; Fannisa Fannisa; Tria Monja Madira (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: Gastritis is an inflammatory condition of the stomach wall, which is caused by irritation of the stomach mucosa and bacterial infections such as Helicobacteri pylory. Bacteria come from contaminated food and drinks. Gastritis causes pain in the sufferer's stomach. Gastritis pain is different for each individual depending on the pain threshold of the sufferer. This pain arises naturally and is something physical or mental. Non-pharmacological measures taken to reduce gastritis pain are with warm compresses. The aim of research on warm compresses is to reduce pain in gastritis patients. The research Method was a case study and was carried out on April 19-21 2025. The subjects in this study were two patients suffering from gastritis, namely 29 years and 56 years. This warm compress is given for 3 days for approximately 15 minutes. The results of the case study showed a decrease in the level of pain after applying a warm compress with a decrease in the moderate pain scale (5-6) to a mild pain scale (0-2). Conclusion: These results show that giving warm compresses is very effective in reducing pain levels in gastritis patients. Applying warm compresses can be an effective and easy way to treat pain in gastritis patients.